Adrenal Medullary Autografts in Anterior Eye Chamber, Lateral Ventricle and Striatum of Adult Rats: A Long Term Study - Shetty, Ashok Kumar (Hindawi Publishing Corporation, 1991)
The neurobiological basis for the short-term recovery in Parkinson's patients and experimental animals grafted with adrenal medulla is not yet clear. Structural details of the grafted chromaffin cells are also not available. In the present study, autografts of adrenal medulla in the anterior eye chamber, lateral ventricle and striatum of adult rats were studied for 360 days. Though a large number of cells degenerated, a few healthy chromaffin cells survived up to 360 days in the anterior eye chamber. In the ventricular and striatal regions, cells degenerated more rapidly, and a few surviving cells were seen only up to 120 and 150 days, respectively. Degeneration of the cells was evident from the alteration of the cytoplasmic granules, appearance of vacuoles and lysosomes, rapid decline in the number of TH and DBH positive cells and diffusion of enzymes in the intercellular region. Only lymphocytes and connective tissue cells were seen in the ventricle after 120 days, while outlines of a few chromaffin cells and background fluorescence were still evident in the striatum up to 150 days. In some of the intrastriatal transplants, morphologically identifiable Schwann cells were present and, in one transplant, there was evidence of myelination of axons by Schwann cells. These axons were obviously derived from the adjacent host tissue. From the findings it has been concluded that autografts of adrenal medulla survive for only a Limited period of time on transplantation to the central nervous system and anterior eye chamber. Survival seemed to be better in the anterior eye chamber than at the sites preferentially chosen for treating Parkinson's patients or experimental animals.